2022
DOI: 10.4103/jwas.jwas_43_22
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the Robson 10-Group Classification System as an Audit Tool in Assessing the Soaring Caesarean Section Rates in Ibadan, Nigeria

Abstract: Background: The caesarean section (CS) is the most common operation performed globally with increased incidence worldwide. Aim and Objectives: Using the Robson 10-Group Classification System (RTGCS), we aimed to identify women who were the main contributors to the high CS rate (CSR) over a 3-year period at a foremost tertiary health facility. Settings: This study was conducted at the Department of Obstetrics and Gynecology, University College… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
3
3
0
Order By: Relevance
“…This is similar to the study done by Bello et al where 62.6% women were multiparous. 10 Most of the women (69.51%) in our study were between 37-42 weeks of gestational age similar to Abubeker et al and Bello et al, where the majority of women belonged to the group more than 37 weeks gestational age. 9,10 In contrast in the study done by Parveen et al in 2021 showed majority of women belonging to less than 37 weeks of gestational age.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is similar to the study done by Bello et al where 62.6% women were multiparous. 10 Most of the women (69.51%) in our study were between 37-42 weeks of gestational age similar to Abubeker et al and Bello et al, where the majority of women belonged to the group more than 37 weeks gestational age. 9,10 In contrast in the study done by Parveen et al in 2021 showed majority of women belonging to less than 37 weeks of gestational age.…”
Section: Discussionsupporting
confidence: 88%
“…10 Most of the women (69.51%) in our study were between 37-42 weeks of gestational age similar to Abubeker et al and Bello et al, where the majority of women belonged to the group more than 37 weeks gestational age. 9,10 In contrast in the study done by Parveen et al in 2021 showed majority of women belonging to less than 37 weeks of gestational age. 11 In the present study 39 (47.57%) women had history of one previous section, 6 (7.31%) had history of two previous sections.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We compared the 48.4% CS rate from this study with that from other public and forprofit private hospital-based studies within Nigeria and across countries and regions that analysed CS using Robson classification system. Within Nigeria, studies in Ibadan (Bello and Agboola, 2022), Ilisan-Remo (Akadiri et al, 2023) and Makurdi (Ochejele et al, 2021) recorded CS rates of 46.9%, 51.2% and 24.3% respectively. In other African countries, hospital-level CS rates varied from as low as 18.2% in Senegal (Mbaye et al, 2015), up to 25.7% in Ethiopia (Tura et al, 2018) and 42.4% in South Africa (Makhanya et al, 2015).…”
Section: Hospital Level Caesarean Section Ratementioning
confidence: 99%
“…Using the Robson classification system, groups of parturients who contribute most and least to CS rates can be identified, and specific group-focused interventions relevant for each health care facility can be adopted. Analysis of hospital-level CS rate on the basis of the Robson classification system is already being carried out in hospitals in Nigeria (Ochejele et al, 2021;Bello and Agboola, 2022;Okonta et al, 2022;Akadiri et al, 2023) and other countries. Country (Kelly et al, 2013;Nakamura-Pereira et al, 2016;Kacerauskiene et al, 2017) and regional (Zeitlin et al, 2021) data is also being published.…”
mentioning
confidence: 99%